Respuesta :
Answer: x = 6, x = -4
Step-by-step explanation:
Find two numbers whose product is the c-value (-24) and sum is the b-value (-2):
0 = x² - 2x - 24
∧
1 -24
2 -12
3 -8
4 -6 = -2 This works!
0 = (x + 4)(x - 6)
Apply the Zero-Product Property (set each factor equal to zero and solve)
0 = x + 4 0 = x - 6
-4 = x 6 = x
The zeros of a function are the value of x, when the function equals 0
The zeros of [tex]\mathbf{p(x) = x^2 - 2x - 24}[/tex] are 6 and -4
The function is given as;
[tex]\mathbf{p(x) = x^2 - 2x - 24}[/tex]
Expand
[tex]\mathbf{p(x) = x^2 +4x- 6x - 24}[/tex]
Factorize
[tex]\mathbf{p(x) = x(x +4)- 6(x + 4)}[/tex]
Factor out x + 4
[tex]\mathbf{p(x) = (x -6)(x + 4)}[/tex]
Set to 0
[tex]\mathbf{(x -6)(x + 4) = 0}[/tex]
Split
[tex]\mathbf{x -6 = 0\ or\ x + 4 = 0}[/tex]
Solve for x
[tex]\mathbf{x = 6\ or\ x = -4}[/tex]
Hence, the zeros of [tex]\mathbf{p(x) = x^2 - 2x - 24}[/tex] are 6 and -4
Read more about zeros of functions at:
https://brainly.com/question/22101211